Efecto de la aplicación de tres dosis de bacterias solubilizadoras de nutrientes en las variedades de papa Capiro y Roja Pancha en la zona de La Libertad, provincia del Carchi - Herembás García, Gonzalo Iván (2013)
In the present study aimed to examine the effect of nutrient solubilizing bacteria (BSN) development and yield of potato varieties Red Capiro iron in Agroforestry Cooperative Alejandro Almeida, San Tander sectors of the Parish of La Libertad Region Mirror, Carchi, in order to evaluate the agronomic performance of two varieties of the potato crop to solubilizing bacteria application of nutrients, identify the most effective dose of bacterial populations on the performance of potato varieties evaluated and analyzed treatments economically. Design was used randomized complete block (RCBD) with factorial arrangement (varieties x dose) with four replications and eight treatments. The experimental plot was 1,408.00 m2 with 20,00 m2 plots being the useful area of 12.00 m2. Variables were evaluated, plant height, stem diameter, number of tubers per plant and tuber yield. All variables were subjected to analysis of variance, using the Tukey pruebaat the 0.05 level of significance to determine the difference between the means of the study factors. The experimental results determined that: improved agronomic characteristics and increased production presents the variety "Red Iron" compared with "Capiro" which is attributed to varietal characteristics. Applying composition 2 - 4 - 6 l / ha BSN variety potato plants "Red iron" and "Capiro" determined that 6 l / ha of the best dosage BSN in increased productivity in the two varieties, excelling "Red iron" with greater increase compared to plants not implemented and with the variety "Red iron" at a dose of 6 l / ha of BSN greatest economic benefit is obtained.